Eruption! : volcanoes and the science of saving lives - Rusch, Elizabeth (Houghton Mifflin Books for Children, 2013)
Follows volcanologists Andy Lockhart and John Pallister as they helicopter onto active volcanoes to install equipment, climb into blast zones to collect ash samples, and endure suspense as they wait to find out if their predictions are accurate.